IMPLEMENTASI CHATBOT SEBAGAI VIRTUAL ASSISTANT PADA PELAYANAN PUBLIK DAN BANTUAN DI DINAS SOSIAL KABUPATEN WONOSOBO DENGAN METODE TF-IDF - Sagita Efendi; Sibyan, Hidayatus; Nur Hasanah (Clean Energy and Smart Technology, 2024)
Information needs are important in public service to give users an initial understanding of the services, the lack of information can make the public service doesn’t work like its function. Based on that reason, a study has been done to create a system that can provides information and assistance on Dinas Sosial PMD at Wonosobo Regency. The study creates chatbot named HADIR bot as a virtual assistant on public services and assistance in Dinas Sosial PMD at Wonosobo regency with TF-IDF method. The goals of this chatbot are to support public service and also virtual assistant that can run 24 hours a day based on the users request or question in chatbot, this chatbot also provides initial description and frequently asked question that often asked to the employees, and provides basic information and document template about list of the assistance. The design of the chatbot uses UML (Unified Modelling Language) like Use Case, Activity Diagram, and Sequence Diagram. This Chatbot created with telegrams features named BotFather, with the function made by Python and text editor uses Visual Studio Code, the chatbot runs in Telegram with TF-IDF method in term weighting and cosine similarity method to evaluate the similarities between document.